Disease development and recovery in resistant and susceptible cassava genotypes infected by African cassava mosaic geminivirus - Njock, T.E.; Atiri, G.I.; Thottappilly, G.; Thresh, J.M. (1996)
(ACMV) were assessed in shoots regenerated from single-node cuttings of three cassava genotypes differing in resistance to ACMV. Plants of the moderately resistant TMS 4(2)1425 and susceptible TMS 60506 did not recover from the disease as rapidly as those of the resistant TMS 30001, Recovery was manifested earlier on leaves of shoots from nodes collected from the shoot tip area than on those from below in all genotypes. Generally, a greater percentage of symptomless plants developed from single-node cuttings obtained from the apical region of infected plants than from the basal region, particularly in the resistant genotype, ACMV was detected serologically at greater concentrations in new axillary shoots regenerating from basal nodes of topped plants of the resistant genotype than from the apical nodes. Symptoms on shoots developing from apical cuttings were also less severe than on those from basal cuttings. Uninfected cuttings were obtained from some plants that had fully recovered from the disease, especially if the cuttings were obtained from young apical tissue.